Numerical Simulation of Hydrogen Sulfide Distribution in the Grille Machine Room of Sewage Treatment Plant - HAN Tianchan; JIANG Yongqing; DONG Zhen; LIU Zhengmei; WANG Rong (Journal of Harbin University of Science and Technology)
Aiming at the problem of hydrogen sulfide pollution in the grille machine room and the poisoning death of operators caused by hydrogen sulfide, by changing the wind direction, room temperature, ventilation mode and other influencing factors, the Fluent numerical simulation method was used to study the distribution of hydrogen sulfide gas concentration in the grille machine room of urban sewage treatment plants and the threshold of hydrogen sulfide concentration exposed to workers during operation. The results show that the highest average concentration distribution of hydrogen sulfide in the grille machine room is only 4. 53 mg/m3 when natural air inlet and mechanical air exhaust are used. During mechanical ventilation, the concentration of hydrogen sulfide exposed to workers working in the grille machine room exceeds 10 mg/m3 , and the maximum concentration can reach 15. 44 mg/m3 . It can be seen that the natural air inlet has a good dilution effect on hydrogen sulfide in the grille machine room, and the closer the natural wind direction is to the door and window orientation the better the dilution effect.